THE EFFECT OF MURABAHAH CONTRACT AND LOCATION ON HOUSING PURCHASE INTENTION WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Cahyadi, H. Aditya; Budi Santoso; Riyanto Setiawan (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The study aims to analyze the influence of murabahah contracts on housing purchase intention with brand image as an intervening variable. Method: The population in this study is all housing consumers who use sharia financing. The researcher used a purposive sampling method with the criteria of consumers who have used murabahah contracts for home financing. The data analysis method used in this study is the Structural Equation Model (SEM). Results: The results of the study show that murabahah contracts have an effect on the brand image of housing. The murabahah contract affects the purchase intention of housing. Novelty: Novelty in the study is brand image as an intervening variable because the company's brand image has a great impact on increasing housing purchase decisions supported by murabahah contracts and location. The benefit of this research is to assist property developers in designing more effective marketing strategies and attracting consumer interest.